Faktor-Faktor Yang Berhubungan Dengan Pemberian ASI Eksklusif Di Puskesmas Rawat Inap Muara Pinang Kabupaten Empat Lawang - Apriani, Rensi; Rohani, Tuti; Darmawansyah, Darmawansyah (Gayaku Publisher, 2023)
Exclusive breastfeeding for babies given by mothers turns out to have an important role, namely increasing the baby's body resistance. Therefore, it can prevent the baby from being attacked by various diseases that can threaten the baby's health. The purpose of this study was to determine the factors associated with exclusive breastfeeding at the Muara Pinang Inpatient Health Center, Empat Lawang Regency. The method used was analytical survey research with a cross sectional research design, data collected in the form of primary data by distributing questionnaires to mothers who have babies aged> 6-12 months at the Muara Pinang Inpatient Health Center, Empat Lawang Regency using simple random sampling technique as many as 57 mothers. Data analysis was performed using the Chi-Square test. The results of univariate analysis showed that more than half of the mothers had less knowledge, more than half of the mothers had working status, more than half of the mothers with unsupportive attitudes and more than half of the mothers whose families did not support. The results of bivariate analysis there is a relationship between maternal knowledge and exclusive breastfeeding (p=0.006), there is a relationship between maternal employment status and exclusive breastfeeding (p=0.028), there is a relationship between maternal attitudes and exclusive breastfeeding (p=0.014) and there is a relationship between family support (husband) with exclusive breastfeeding (p=0.026). Researchers suggest to the health center that the results of this study can be used as additional data for the Inpatient Health Center in increasing the achievement of exclusive breastfeeding